The Glutaredoxin Gene, grxB, Affects Acid Tolerance, Surface Hydrophobicity, Auto-Aggregation, and Biofilm Formation in Cronobacter sakazakii - Ling, Na; Zhang, Jumei; Li, Chengsi; Zeng, Haiyan; He, Wenjing; Ye, Yingwang; Wu, Qingping (Frontiers in Microbiology, 2018)
Cronobacter species are foodborne pathogens that cause neonatal meningitis, necrotizing enterocolitis and sepsis; they have unusual abilities to survive in environmental stresses such as acid stress. However, the factors involved in acid stress responses and biofilm formation of Cronobacter species are poorly understood. In this study, we investigated the roles of grxB on cellular morphology, acid tolerance, surface hydrophobicity, auto-aggregation, motility and biofilm formation in Cronobacter sakazakii. The deletion of grxB decreased resistance to acid stresses, and notably led to weaker surface hydrophobicity, auto-aggregation and biofilm formation under normal and acid stress conditions, but not motility, compared with those of the wild type strain. Therefore, grxB appears to contribute to survival of C. sakazakii in acid stresses and biofilm formation. This is the first report to provide valuable evidence for the roles of grxB in acid stress responses and biofilm formation in C. sakazakii.